Identical Structural and Receptor Binding Defects in Apolipoprotein E2 in Hypo-, Normo-, and Hypercholesterolemic Dysbetalipoproteinemia - Rall, Stanley C. (1983)
Apolipoprotein E (apoprotein E or apo-E) from type III hyperlipoproteinemic subjects with the E2/2 homozygous phenotype displays both structural and receptor binding heterogeneity. The apo-E from all subjects thus far studied, however, has been functionally defective, though to different degrees. Although nearly every type III hyperlipoproteinemic subject has the E2/2 phenotype, 95-99% of the people with this same phenotype do not display type III hyperlipoproteinemia, nor do they have elevated plasma cholesterol levels. Consequently, it became important to determine whether the apo-E2 from hypo- and normocholesterolemic individuals with the E2/2 phenotype is also functionally abnormal. To do this, apo-E2 was isolated from two hypo-, two normo- and two hypercholesterolemic homozygous E2/2 subjects. The apo-E2 was recombined with vesicles and tested for its ability to displace (125)I-low density lipoproteins (LDL) from apo-B,E (LDL) receptors on human fibroblasts. The apo-E2 from all six subjects was found to be severely defective in receptor binding (<2% of the binding activity of normal apo-E3). In all cases, the binding activity of the apo-E2 was increased 10- to 20-fold by treating the apoproteins with cysteamine, a reagent that converts cysteine residues to positively charged lysine analogues. The cysteine content of each apo-E was determined by monitoring the change in the isoelectric focusing position of the cysteamine-treated apo-E2. Using this method, it was found that the apo-E2 from each subject contained two cysteine residues per mole. A partial sequence analysis of the cysteine-containing regions of the apo-E from three of the six subjects indicated that the two cysteine residues were at residues 112 and 158 in the amino acid sequence. The cysteine at residue 158 has previously been implicated in the severe binding defect of the apo-E2 from a type III hyperlipoproteinemic subject. Since the apo-E2 of the hypo-, normo-, and hypercholesterolemic subjects in this study all displayed a severe functional abnormality, it is apparent that factors in addition to the defective receptor binding activity of the apo-E2 are necessary for the manifestation of type III hyperlipoproteinemia.